Optimalitas Perancangan Website: Pendekatan User Centered Design untuk Pengalaman Pengguna Berbagai Usia di Situs Jalan Cantik - Ardra Maulana Adwitiya Nugroho; Suprihadi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
In the digital age, a deep understanding of user experience (UX) and user interface (UI) is crucial for enhancing user satisfaction. This research explores the application of User Centered Design (UCD) in designing the